Magnetic response Janus-MoS2 nanosheet as well as preparation method and application thereof

By preparing magnetically responsive Janus-MoS2 nanosheets, the problem of difficulty in deploying and recycling nanomaterials in oil extraction is solved, the crude oil recovery rate and oil displacement efficiency are improved, and the cost is reduced.

CN119118199APending Publication Date: 2024-12-13CHANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411012612.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-26
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing nanomaterials cannot be intelligent and targeted deployment and recycling in petroleum exploitation, resulting in low oil displacement efficiency and waste of resources, and few research on MoS2 magnetically responsive nanomaterials.

Method used

Magnetic responsive Janus-MoS2 nanosheets were prepared by adding MoS2 to a mixed solution of ethanol and deionized water. Magnetic responsive nanosheets were formed by reaction of iron salt and ammonia water, and secondary modification was performed by hydrophobic and hydrophilic modifiers. Nanosheets with amphiphilicity and magnetic responsiveness were obtained.

Benefits of technology

The rapid migration and targeted control of nanosheets at the oil-water interface are achieved, which improves crude oil recovery rate, is easy to recover and reuse, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118199A_ABST
    Figure CN119118199A_ABST
Patent Text Reader

Abstract

The invention discloses a magnetic response Janus-MoS2 nanosheet as well as a preparation method and application thereof, and belongs to the technical field of oil exploitation. The preparation method comprises the following steps: quickly adding ammonia water into a mixed solution of an iron salt solution and a MoS2 dispersion liquid, reacting, centrifuging, washing and drying to obtain a magnetic response MoS2 nanosheet; the preparation method comprises the following steps: adding the magnetic response MoS2 nanosheet into a mixed solution of a hydrophobic modifier and a hydrophilic modifier, and then stirring, centrifuging, washing and drying to obtain the magnetic response Janus-MoS2 nanosheet. The magnetic response Janus-MoS2 nanosheet prepared by the preparation method disclosed by the invention has amphipathicity and special magnetic responsiveness. Due to the oil-water amphiphilic structural characteristic, the nanosheet can be quickly migrated to an oil-water interface, and residual oil after water flooding is effectively displaced. Due to the magnetic responsiveness, the nanosheets can realize targeted control in the oil displacement process, so that the crude oil recovery rate is further improved, and the nanosheets are easy to recover and reuse after oil displacement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oil extraction, and specifically relates to a magnetically responsive Janus-MoS2 nanosheet and a preparation method and application thereof. Background Art

[0002] Nanofluids, as a new type of low-cost, environmentally friendly oil displacement agent, have been widely studied in recent years. Research on nanofluid injection and production enhancement technology is of great significance to oil field production, especially for low-permeability oil field production. A large number of literature reports that nanofluids have the ability to stabilize emulsions, reduce interfacial tension and wettability inversion, and can significantly improve crude oil recovery. Compared with traditional homogeneous spherical nanoparticles, amphiphilic Janus nanosheets have become more widely studied in improving oil recovery due to their good interfacial activity. Among them, the most common is graphene-based amphiphilic Janus nanosheets, and a large number of studies have fully affirmed its excellent oil displacement performance. However, the high price of graphene limits its further development in the field of improving oil recovery.

[0003] As an emerging two-dimensional nanomaterial, MoS2 has a structure similar to graphene nanosheets, but its application cost is much lower than that of graphene, and MoS2 has been proven to help improve crude oil recovery in the oil field. The modified MoS2 can be adsorbed on the oil-water interface to form an elastic interface film, which reduces the oil-water interfacial tension and achieves the effect of oil displacement under the action of fluid flow. However, conventional nanomaterials cannot be deployed in an intelligent and targeted manner after being injected into the reservoir. Nanoparticles easily clog the formation, resulting in a slow and inefficient oil displacement process. At the same time, conventional nanomaterials are not easy to recycle, which will also cause a large waste of resources and high oil displacement costs.

[0004] The introduction of smart responsive nanomaterials gives nanomaterials targetedness and intelligence, providing a new idea for the control and recovery of nanoparticles in reservoirs. By modifying the surface function of the material or changing the template material, the nanomaterial can have additional functions, such as magnetic response, pH response and temperature response characteristics, so that nanofluids can exploit oil reserves that cannot be exploited using conventional methods and achieve targeted deployment and reuse of nanoparticles in underground reservoirs. At present, most of the research on the intelligent design of nanomaterials focuses on pH response and temperature responsiveness. There are few reports on the synthesis of magnetic responsive nanomaterials of MoS2 nanosheets to improve oil recovery and achieve control and reuse of nanoparticles. In view of this, we propose a simple and low-cost synthesis strategy for the preparation of magnetic responsive Janus-MoS2 nanosheets, which is of great significance for the development of nanofluid oil recovery technology. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing magnetically responsive Janus-MoS2 nanosheets.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions, including: adding MoS2 to a mixed solution of ethanol and deionized water, and mixing them uniformly to obtain a MoS2 dispersion; dissolving ferric chloride hexahydrate and ferrous chloride tetrahydrate in deionized water, and mixing them uniformly to obtain an iron salt solution;

[0009] The iron salt solution and the MoS2 dispersion are mixed and stirred evenly at one time to obtain a mixed solution, and stirred at a predetermined temperature for a predetermined time;

[0010] Ammonia water is quickly added to the mixture to react, and then centrifuged, washed, and dried to obtain magnetically responsive MoS2 nanosheets;

[0011] The magnetically responsive MoS2 nanosheets are added into a mixed solution of a hydrophobic modifier and a hydrophilic modifier, and then stirred, centrifuged, washed and dried for a second time to obtain magnetically responsive Janus-MoS2 nanosheets.

[0012] As a preferred scheme for the preparation method of the magnetic responsive Janus-MoS2 nanosheets described in the present invention, wherein: the mass concentration of the MoS2 dispersion is 0.5-3 mg / mL, and the mass ratio of the ethanol and deionized water is 1:1; the mass concentration of the iron salt solution is 15-90 mg / mL, and the mass ratio of the ferric chloride hexahydrate and ferrous chloride tetrahydrate is 2:1.

[0013] As a preferred scheme of the preparation method of the magnetic responsive Janus-MoS2 nanosheets described in the present invention, the mass ratio of the iron salt solution to the MoS2 dispersion is 1:2-5; the single stirring, wherein the stirring temperature is 60-80°C, the stirring speed is 500-1000rpm, and the stirring time is 0.5-2h.

[0014] As a preferred scheme of the preparation method of the magnetic responsive Janus-MoS2 nanosheets described in the present invention, the mass ratio of the ammonia water to the mixed liquid is 1:20-50, the reaction temperature is 100°C, and the reaction time is 1-3h.

[0015] As a preferred scheme of the preparation method of the magnetically responsive Janus-MoS2 nanosheets described in the present invention, wherein: the mass ratio of the hydrophobic modifier solution to the hydrophilic modifier solution in the mixed solution of the hydrophobic modifier and the hydrophilic modifier is 1:2~5.

[0016] As a preferred scheme of the preparation method of the magnetic responsive Janus-MoS2 nanosheets described in the present invention, wherein: the hydrophobic modifier includes one or more of tetradecylamine, hexadecylamine or octadecylamine, the solvent is anhydrous ethanol, and the solution concentration is 1 to 5 mg / mL; the hydrophilic modifier includes one or more of glutamic acid or aspartic acid, the solvent is deionized water, and the solution concentration is 1 to 10 mg / mL.

[0017] As a preferred scheme of the preparation method of the magnetic responsive Janus-MoS2 nanosheets described in the present invention, wherein: the mass concentration of the magnetic responsive MoS2 nanosheets in the mixed solution is 1-10 mg / mL, and the secondary stirring, wherein the stirring speed is 500-1000 rpm, and the stirring time is 5-12 h.

[0018] As a preferred scheme of the preparation method of the magnetic responsive Janus-MoS2 nanosheets described in the present invention, wherein: the washing is performed by alternating washing with water and anhydrous ethanol for 2 to 4 times in sequence; the drying temperature is 60 to 80°C.

[0019] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a magnetically responsive Janus-MoS2 nanosheet having amphiphilicity and good magnetic responsiveness.

[0020] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a magnetically responsive Janus-MoS2 nanosheet for use as a nano-oil-displacing material in oil production.

[0021] Beneficial effects of the present invention:

[0022] (1) The magnetically responsive Janus-MoS2 nanosheets prepared by the present invention have amphiphilicity and special magnetic responsiveness. The oil-water amphiphilic structural characteristics enable the nanosheets to quickly migrate to the oil-water interface and effectively displace the residual oil after water flooding. The magnetic responsiveness enables the nanosheets to achieve targeted control during the oil flooding process, thereby further improving the oil recovery rate, and the nanosheets are easy to recover and reuse after oil flooding.

[0023] (2) The raw materials used in the present invention are easily available, low in cost, and the preparation method is simple, which is suitable for large-scale industrial production.

[0024] (3) The present invention utilizes amino acids to perform hydrophilic modification on the nanosheets, which is green and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them:

[0026] Figure 1 This is a flow chart for the preparation of the magnetically responsive Janus-MoS2 nanosheets of the present invention.

[0027] Figure 2 This is the infrared spectrum of the magnetically responsive Janus-MoS2 nanosheets in Example 1.

[0028] Figure 3 This is the magnetic response test diagram of the magnetically responsive Janus-MoS2 nanosheets in Example 1.

[0029] Figure 4 The oil-water interfacial tension test diagram of the magnetically responsive Janus-MoS2 nanosheet in Example 1

[0030] Figure 5 This is a test diagram of the oil recovery performance of the magnetically responsive Janus-MoS2 nanosheets in Example 1. DETAILED DESCRIPTION

[0031] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0032] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0033] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0034] The raw materials used in the present invention are all commercially available unless otherwise specified.

[0035] The material prepared in the embodiment of the present invention was tested for oil displacement performance according to the following method:

[0036] The magnetically responsive Janus-MoS2 nanosheets were added to deionized water, and a nanofluid with a concentration of 0.005wt% was prepared by ultrasonic dispersion for core displacement experiments. The artificial core used had a diameter of 2.5cm, a length of 10cm, and a permeability of 700mD; the viscosity of the crude oil used was 40mPa·s at 60°C. The steps of the core displacement experiment are as follows: ① Inject crude oil into the water-saturated core, and then age it at 70°C for 24h. ② Start injecting water into the core until the water content is greater than 98%, and then inject 0.5PV magnetically responsive Janus-MoS2 nanofluid. ③ Finally, inject water again until the water content is greater than 98%. The temperature during the entire experiment was 60°C. During the nanofluid displacement process, two magnetic plates were placed on both sides of the core, and the magnetic field strength was controlled by adjusting the distance between the two plates.

[0037] Example 1

[0038] This embodiment provides a method for preparing magnetically responsive Janus-MoS2 nanosheets, referring to Figure 1 , specifically:

[0039] Preparation of magnetically responsive MoS2 nanosheets:

[0040] (1) adding 100 mg MoS2 to a mixed solution of 50 mL ethanol and 50 mL deionized water, and obtaining a MoS2 dispersion after ultrasonic dispersion, i.e., the mass concentration of the MoS2 dispersion is 1 mg / mL;

[0041] Dissolve 600 mg of ferric chloride hexahydrate and 300 mg of ferrous chloride tetrahydrate in 20 mL of deionized water, and stir thoroughly to obtain an iron salt solution, i.e., the concentration of the iron salt solution is 45 mg / mL;

[0042] (2) Mix the iron salt solution and the MoS2 dispersion at a mass ratio of 1:3, set the speed to 700 rpm, and stir magnetically at 60 °C for 1 h;

[0043] (3) Ammonia water was quickly added to the mixture at a mass fraction of 3%, and the mixture was reacted at 100°C for 2 hours. The mixture was then centrifuged and washed alternately with water and anhydrous ethanol for three times. Finally, the mixture was placed in a constant temperature drying oven at 70°C and dried to constant weight to obtain magnetically responsive MoS2 nanosheets.

[0044] Preparation of magnetically responsive Janus-MoS2 nanosheets:

[0045] (1) dissolving 20 mg of octadecylamine in 10 mL of anhydrous ethanol to obtain a hydrophobic modifier solution with a concentration of 2 mg / mL; dissolving 100 mg of glutamic acid in 20 mL of deionized water to obtain a hydrophilic modifier solution with a concentration of 5 mg / mL; then mixing the prepared hydrophobic and hydrophilic modifier solutions in a mass ratio of 1:3 and stirring them uniformly;

[0046] (2) Add 150 mg of magnetically responsive MoS2 nanosheets to a mixed solution of hydrophobic and hydrophilic modifiers, set the rotation speed to 700 rpm, and magnetically stir at room temperature for 12 h. Then, centrifuge and wash alternately with water and anhydrous ethanol for 3 times. Finally, place in a constant temperature drying oven at 70°C and dry to constant weight to obtain magnetically responsive Janus-MoS2 nanosheets.

[0047] The infrared curves of magnetically responsive MoS2 nanosheets and magnetically responsive Janus-MoS2 nanosheets are shown in Figure 2 . Figure 2 In the figure, both infrared curves are at 1029cm -1 、798cm -1 The characteristic absorption peak at 555cm is caused by the stretching vibration of Mo=O and Mo-S functional groups, indicating that the main component of the sample is MoS2. -1 An obvious Fe-O bond characteristic peak can be observed at 2921 cm-1, which indicates that Fe3O4 is successfully grafted onto the MoS2 surface. -1 and 2851cm -1 The characteristic absorption peak at 555 cm-1 is caused by the asymmetric and symmetric vibration of -CH2 in the alkylamine group, which proves the successful grafting of octadecylamine. In addition, the magnetic responsive Janus-MoS2 nanosheets have a -1 and 477cm -1 The reason for the large peak is the overall vibration of the -NH2 group and -COOH group on glutamic acid. -1 The characteristic absorption peak at also proves the existence of -COOH groups. The above information shows that Fe3O4, octadecylamine and glutamic acid are successfully grafted onto MoS2 nanosheets.

[0048] The magnetic properties of the magnetically responsive Janus-MoS2 nanosheets were tested by magnet detection method. Figure 3 As shown, the nanosheets originally dispersed in the water were quickly attracted to one side of the magnet after the magnet was added, which shows that the magnetically responsive Janus-MoS2 nanosheets have excellent magnetic properties, and the addition of a certain magnetic field can change the flow direction of the nanosheets in the water.

[0049] The performance test results of magnetically responsive Janus-MoS2 nanosheets in reducing oil-water interfacial tension are shown in Figure 4 . Take a certain amount of magnetic responsive Janus-MoS2 nanosheets and add them to deionized water, and prepare nanodispersions of different concentrations by ultrasonic dispersion. Take 15mL of magnetic responsive Janus-MoS2 nanosheet dispersion and 25mL of paraffin oil and add them to a beaker to form a two-phase system, and then use the QBZY series fully automatic surface tension meter (platinum plate method) to test the oil-water interfacial tension of the system. Figure 4 As shown in the figure, with the increase of nanosheet concentration, the interfacial tension of the system gradually decreases, indicating that the prepared magnetically responsive Janus-MoS2 nanosheets can reduce the oil-water interfacial tension and have good interfacial properties.

[0050] The oil displacement performance test results of magnetic response Janus-MoS2 nanosheets are shown in Figure 5 It can be seen that after water flooding, the oil recovery rate only reached 31.96%, and the oil recovery effect was poor. After the injection of nanofluid, the oil recovery rate further increased to 43.4%, until the subsequent water flooding ended, the recovery rate reached 51.82%. The magnetically responsive Janus-MoS2 nanofluid can significantly increase the oil recovery rate by 19.86%.

[0051] Example 2

[0052] The difference between this embodiment and Example 1 is that the amount of MoS2 is adjusted to 50 mg, that is, the mass concentration of the MoS2 dispersion is 0.5 mg / mL, and the rest of the preparation process is the same as that of Example 1 to obtain magnetically responsive Janus-MoS2 nanosheets.

[0053] Example 3

[0054] The difference between this embodiment and Example 1 is that the amount of MoS2 is adjusted to 300 mg, that is, the mass concentration of the MoS2 dispersion is 3 mg / mL, and the rest of the preparation process is the same as that of Example 1 to obtain magnetically responsive Janus-MoS2 nanosheets.

[0055] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 1.

[0056] Table 1 Performance evaluation results of magnetically responsive Janus-MoS2 nanosheets

[0057] Dosage (wt%) <![CDATA[Oil-water interfacial tension (10 -2 mN / m)]]> Improved oil recovery (%) Example 1 0.005 11.25 19.86 Example 2 0.005 20.74 10.44 Example 3 0.005 12.67 13.73

[0058] As can be seen from the above table, adjusting the amount of MoS2 has a significant effect on the performance of magnetically responsive Janus-MoS2 nanosheets. When the amount of MoS2 is relatively small compared to iron salts, a large amount of Fe3O4 attached to the surface of MoS2 will affect the grafting of hydrophobic and hydrophilic modifiers, resulting in reduced interfacial activity of the nanosheets and reduced effect of improving oil recovery; conversely, when the amount of MoS2 is large, the Fe3O4 attached to its surface decreases, the magnetic response of the particles decreases, and the effect of improving oil recovery decreases. According to the results in the above table, the best technical effect can be obtained when the MoS2 concentration in the present invention is 1 mg / mL.

[0059] Example 4

[0060] The difference between this embodiment and Example 1 is that the dosage of ferric chloride hexahydrate and ferrous chloride tetrahydrate is adjusted to 200 mg and 100 mg respectively, so that the concentration of the iron salt solution is 15 mg / mL. The rest of the preparation process is the same as that of Example 1, and magnetically responsive Janus-MoS2 nanosheets are obtained.

[0061] Example 5

[0062] The difference between this embodiment and Example 1 is that the dosage of ferric chloride hexahydrate and ferrous chloride tetrahydrate is adjusted to 1266.7 mg and 633.3 mg so that the concentration of the iron salt solution is 90 mg / mL. The rest of the preparation process is the same as that of Example 1 to obtain magnetically responsive Janus-MoS2 nanosheets.

[0063] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 2.

[0064] Table 2 Performance evaluation results of magnetically responsive Janus-MoS2 nanosheets

[0065] Dosage (wt%) <![CDATA[Oil-water interfacial tension (10 -2 mN / m)]]> Improved oil recovery (%) Example 1 0.005 11.25 19.86 Example 4 0.005 13.15 11.27 Example 5 0.005 22.68 10.84

[0066] As can be seen from the above table, adjusting the concentration of the iron salt solution has a significant effect on the performance of the magnetically responsive Janus-MoS2 nanosheets. When the iron salt concentration is too high, it will affect the grafting of hydrophobic and hydrophilic modifiers, resulting in reduced interfacial activity of the nanoparticles and reduced effect of improving oil recovery; conversely, the magnetic response of the particles is reduced, and the effect of improving oil recovery is reduced. According to the results in the above table, the best technical effect can be obtained when the concentration of the iron salt solution in the present invention is 45 mg / mL.

[0067] Example 6

[0068] The difference between this embodiment and Example 1 is that the type of hydrophobic modifier is adjusted to hexadecylamine, and the rest of the preparation process is the same as that of Example 1 to obtain magnetically responsive Janus-MoS2 nanosheets.

[0069] Example 7

[0070] The difference between this embodiment and Example 1 is that the type of hydrophobic modifier is adjusted to tetradecylamine, and the rest of the preparation process is the same as that of Example 1 to obtain magnetically responsive Janus-MoS2 nanosheets.

[0071] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 3.

[0072] Table 3 Performance evaluation results of magnetically responsive Janus-MoS2 nanosheets

[0073]

[0074]

[0075] It can be seen from the above table that adjusting the type of hydrophobic modifier has a significant effect on the performance of magnetically responsive Janus-MoS2 nanosheets. This is because the longer the alkyl chain, the more conducive it is to the hydrophobic modification of the nanosheets. According to the results in the above table, the best technical effect can be obtained when the alkylamine in the present invention is octadecylamine.

[0076] Example 8

[0077] The difference between this embodiment and Example 1 is that the amount of octadecylamine is adjusted to 10 mg, that is, the concentration of the hydrophobic modifier is 1 mg / mL, and the rest of the preparation process is the same as that of Example 1 to obtain magnetically responsive Janus-MoS2 nanosheets.

[0078] Example 9

[0079] The difference between this embodiment and Example 1 is that the amount of octadecylamine is adjusted to 50 mg, that is, the concentration of the hydrophobic modifier is 5 mg / mL, and the rest of the preparation process is the same as that of Example 1 to obtain magnetically responsive Janus-MoS2 nanosheets.

[0080] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 4.

[0081] Table 4 Performance evaluation results of magnetically responsive Janus-MoS2 nanosheets

[0082] Dosage (wt%) <![CDATA[Oil-water interfacial tension (10 -2 mN / m)]]> Improved oil recovery (%) Example 1 0.005 11.25 19.86 Example 8 0.005 14.28 13.25 Example 9 0.005 17.38 11.37

[0083] It can be seen from the above table that adjusting the amount of alkylamine has a significant effect on the performance of magnetically responsive Janus-MoS2 nanosheets. This is because the amount of alkylamine determines the hydrophobicity of the nanosheets. Appropriate hydrophobic modification is more conducive to the nanosheets to obtain amphiphilicity. According to the results in the above table, the best technical effect can be obtained when the amount of alkylamine in the present invention is 2 mg / mL.

[0084] Example 10

[0085] The difference between this embodiment and Example 1 is that the amount of glutamic acid is adjusted to 20 mg, that is, the concentration of the hydrophilic modifier is 1 mg / mL, and the rest of the preparation process is the same as that of Example 1 to obtain magnetically responsive Janus-MoS2 nanosheets.

[0086] Embodiment 11

[0087] The difference between this embodiment and Example 1 is that the amount of glutamate is adjusted to 200 mg, that is, the concentration of the hydrophilic modifier is 10 mg / mL, and the rest of the preparation process is the same as that of Example 1 to obtain magnetically responsive Janus-MoS2 nanosheets.

[0088] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 5.

[0089] Table 5 Performance evaluation results of magnetic response Janus-MoS2 nanosheets

[0090] Dosage (wt%) <![CDATA[Oil-water interfacial tension (10 -2 mN / m)]]> Improved oil recovery (%) Example 1 0.005 11.25 19.86 Example 10 0.005 18.35 11.96 Embodiment 11 0.005 16.63 12.46

[0091] It can be seen from the above table that adjusting the dosage of the hydrophilic modifier has a significant effect on the performance of the magnetically responsive Janus-MoS2 nanosheets. This is because the dosage of the hydrophilic modifier determines the hydrophilicity of the nanosheets. Appropriate hydrophilic modification is more conducive to the nanosheets to obtain amphiphilicity. According to the results in the above table, the best technical effect can be obtained when the concentration of the amino acid in the present invention is 5 mg / mL.

[0092] Comparative Example 1

[0093] This comparative example provides a method for preparing a conventional nanosheet, specifically:

[0094] Preparation of modifier 1-2: Weigh 28.75g of octylphenol polyoxyethylene ether-4 (OP-4), add it to dichloromethane, pour it into a 500mL three-necked flask, add 9.74g of triethylamine, stir in an ice-water bath until the temperature is 0°C, stir the solution at room temperature at a speed of 400r / min, slowly drop a dichloromethane solution containing 15g of p-toluenesulfonyl chloride at a speed of 1.5mL / min, and stir and react at room temperature for 26h. After the reaction is completed, use dilute hydrochloric acid to adjust the pH to 6, wash twice with saturated brine, and perform vacuum distillation at 60°C to obtain the intermediate product. Slowly add the intermediate product to 85mL of ammonia water, stir and react at 30°C at a speed of 400r / min for 26h, gradually heat to 55°C after the reaction, and continue to stir and react at a speed of 400r / min for 26h. After the reaction, the reaction solution was extracted with dichloromethane, and the organic phase was collected, washed twice with saturated brine, and distilled under reduced pressure at 60° C. to obtain the target product.

[0095] Preparation of modifier 2-1: Weigh 28.75g fatty alcohol polyoxyethylene ether-20 (Pingpingjia 0-20), add it to dichloromethane, pour it into a 500mL three-necked flask, add 9.74g triethylamine, stir in an ice-water bath until the temperature is 0°C, stir the solution at room temperature at 400r / min, slowly drop a dichloromethane solution containing 15g p-toluenesulfonyl chloride at a rate of 1.5mL / min, and stir and react at room temperature for 26h. After the reaction is completed, use dilute hydrochloric acid to adjust the pH to 6, wash twice with saturated brine, and perform vacuum distillation at 60°C to obtain the intermediate product. Slowly add the intermediate product to 80ml ammonia water, stir and react at 30°C at 400r / min for 26h, gradually heat to 55°C after the reaction, and continue to stir and react at 400r / min for 26h. After the reaction, the reaction solution was extracted with dichloromethane, and the organic phase was collected, washed twice with saturated brine, and distilled under reduced pressure at 60° C. to obtain the target product.

[0096] Preparation of nanosheet oil-displacing agent: 1.0 g of molybdenum disulfide nanosheets, 0.8 g of modifier 1-2 and 0.2 g of modifier 2-1 were dispersed in anhydrous ethanol, and the solution was ultrasonically shaken for 60 min to form a uniform dispersion, and the dispersion was stirred at 65 ° C and 500 r / min for 30 h, and then dried and purified to obtain modified nanosheets.

[0097] Comparative Example 2

[0098] The difference between this comparative example and Example 1 is that the amount of MoS2 is adjusted to 400 mg, that is, the mass concentration of the MoS2 dispersion is 4 mg / mL, and the rest of the preparation process is the same as that of Example 1 to obtain magnetically responsive Janus-MoS2 nanosheets.

[0099] Comparative Example 3

[0100] The difference between this comparative example and Example 1 is that the amount of octadecylamine is adjusted to 5 mg, and the rest of the preparation process is the same as Example 1 to obtain magnetically responsive Janus-MoS2 nanosheets.

[0101] The performance of the material obtained in the above comparative example was tested, and the comparison results with those of Example 1 are shown in Table 5.

[0102] Table 6 Nanosheet performance evaluation results

[0103] Dosage (wt%) Mineralization (mg / L) Improved oil recovery (%) Example 1 0.005 0 19.86 Comparative Example 1 0.05 0 12.96 Comparative Example 2 0.005 0 8.45 Comparative Example 3 0.005 0 7.23

[0104] It can be seen from the above table that the nanofluid prepared in Example 1 has a better effect of improving oil recovery than those in Comparative Examples 1-3, which is attributed to the excellent interfacial activity and magnetic response characteristics of the nanofluid in Example 1, which helps to achieve efficient oil displacement.

[0105] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A magnetically responsive Janus-MoS 2 Preparation method of nanosheets, Features: include, MoS 2 Add to the mixed solution of ethanol and deionized water, mix well to obtain MoS 2 Dispersion liquid; dissolving ferric chloride hexahydrate and ferrous chloride tetrahydrate in deionized water, and mixing them evenly to obtain an iron salt solution; Iron salt solution and MoS 2 The dispersions are mixed and stirred uniformly at one time to obtain a mixed solution, which is stirred at a predetermined temperature for a predetermined time; Ammonia water is quickly added to the mixture to react, and then centrifuged, washed, and dried to obtain magnetically responsive MoS 2 Nanosheets; The magnetically responsive MoS 2 The nanosheets were added to a mixed solution of a hydrophobic modifier and a hydrophilic modifier, and then stirred, centrifuged, washed, and dried to obtain magnetically responsive Janus-MoS 2 Nanosheets.

2. The magnetically responsive Janus-MoS as claimed in claim 1 2 Preparation method of nanosheets, Features: The MoS 2 The mass concentration of the dispersion is 0.5-3 mg / mL, the mass ratio of ethanol to deionized water is 1:1; the mass concentration of the iron salt solution is 15-90 mg / mL, the mass ratio of ferric chloride hexahydrate to ferrous chloride tetrahydrate is 2:1, and the iron salt solution and MoS 2 The mass ratio of the dispersion is 1:2-5.

3. The magnetically responsive Janus-MoS according to claim 1 2 Preparation method of nanosheets, Features: The primary stirring has a stirring temperature of 60 to 80° C., a stirring speed of 500 to 1000 rpm, and a stirring time of 0.5 to 2 h.

4. The magnetically responsive Janus-MoS according to claim 1 2 Preparation method of nanosheets, Features: The mass ratio of the aqueous ammonia to the mixed liquid is 1:20-50, the reaction temperature is 100° C., and the reaction time is 1-3 hours.

5. The magnetically responsive Janus-MoS as claimed in claim 1 2 Preparation method of nanosheets, Features: The mass ratio of the hydrophobic modifier solution to the hydrophilic modifier solution in the mixed solution of the hydrophobic modifier and the hydrophilic modifier is 1:2-5.

6. The magnetically responsive Janus-MoS as claimed in claim 5 2 Preparation method of nanosheets, Features: The hydrophobic modifier includes one or more of tetradecylamine, hexadecylamine or octadecylamine, the solvent is anhydrous ethanol, and the solution concentration is 1 to 5 mg / mL; the hydrophilic modifier includes one or more of glutamic acid or aspartic acid, the solvent is deionized water, and the solution concentration is 1 to 10 mg / mL.

7. The magnetically responsive Janus-MoS as claimed in claim 1 2 Preparation method of nanosheets, Features: The magnetically responsive MoS 2 The mass concentration of the nanosheets in the mixed solution is 1-10 mg / mL; the secondary stirring has a rotation speed of 500-1000 rpm and a stirring time of 5-12 hours.

8. The magnetically responsive Janus-MoS as claimed in claim 1 2 Preparation method of nanosheets, Features: The washing is performed by washing with water and anhydrous ethanol alternately for 2 to 4 times; the drying temperature is 60 to 80°C.

9. A magnetically responsive Janus-MoS prepared by the method according to any one of claims 1 to 8 2 Nanosheets, Features: The magnetically responsive Janus-MoS 2 The nanosheets are amphiphilic and have good magnetic responsiveness.

10. A magnetically responsive Janus-MoS as claimed in claim 9 2 Application of nanosheets as nano oil recovery materials in oil extraction.